Quantifying internal CO2 recycling for high-rate carbon capture in mixotrophic Scenedesmus acuminatus - Muhammad Muzammil Sultan; Muhammad Mubashar; Hira Ashfaq; Jing Li; Xuezhi Zhang (Bioresource Technology, 2026)

Growth dynamics and disease resistance of cluster beans were associated with antioxidant enzymes feedback against soil rhizospheric pathogens - Muhammad Waseem Abbasi; Sabina Parveen; Ishrat Jahan; Qu Wei; Marium Tariq; Muhammad Azeem; Mubashar Raza; Muhammad Javed Zaki; Majid Sharifi-Rad (Acta Physiologiae Plantarum, 2026)

Erratum to: CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

The Fragile Sink: Reconceptualizing Soil Carbon Stabilization and Its Vulnerability Under Global Change - Muhammad Mubashar Iqbal; Muhammad Ansar Farooq; Rattan Lal; Mohamed Abdalla; Pete Smith (Global Change Biology, 2026)
Soil carbon sequestration (SC seq ) is fundamental to global climate mitigation initiatives; however, growing evidence indicates an expanding disparity between carbon (C) accumulation and its long‐term persistence. This article aims to integrate recent advances in microbial ecology, mineral biogeochemistry, and nutrient stoichiometry to examine why increases in soil C (SC) stocks do not necessarily translate into long‐term persistence. The article introduces the fragile sink framework, wherein sink durability reflects the balance between internal C throughput and the strength of stabilizing barriers. Global change drivers, including warming, elevated CO 2 (eCO 2 ), nutrient enrichment, and anthropogenic disturbance, can accelerate internal C turnover, resulting in soils that are structurally younger, more reactive, and increasingly vulnerable to rapid C loss despite stable or rising stocks. The article shows that destabilization begins at predictable vulnerability frontiers where stoichiometric gating and mineral protection are overridden, while recovery is constrained by kinetic and architectural hysteresis. Thus, it recommends a shift away from stock‐ and input‐centric C farming toward process‐centric C defense, emphasizing the protection of slow‐cycling, kinetically protected pools under increasing turnover.

Unraveling volcanic cooling in semi-arid climates: model–observation gaps and multi-eruption impacts over Iran - Gholamreza Roshan; Abdolazim Saman; Stefan W. Grab; Muhammad Mubashar Dogar; Shingo Watanabe; Tarig A. Ali (Natural Hazards, 2026)

GPC climate/atmosphere section remit - Alan Haywood; Muhammad Mubashar Dogar; Ran Feng; Gabriel Pontes; Christian Stepanek (Global and Planetary Change, 2026)

CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

Heat and humidity stress aggravate high-fat diet-induced kidney damage in albino rats - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad-Ur-Rahman (Biologia Futura, 2026)

Biochemical and histological alterations in the liver of albino rats fed a carbohydrate-rich diet under chronic heat and humidity stress - Robina Shaukat; Muhammad Mubashar Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad-Ur-Rahman (Biologia Futura, 2026)

Assessment of Protective Role of Different Probiotic Strains against Bacterial and Endotoxin-Induced Sepsis in a Mouse Model - Sabeeka Sajjal; Hasnat Ahmad Bilal; Ambreen Zahra; Ayesha Saeed; Aiman Khan; Muhammad Musa Mubashar; Aisha Khatoon; Muhammad Imran Arshad (Probiotics and Antimicrobial Proteins, 2026)

Mixotrophic microalgae-based wastewater nutrient removal: A systematic analysis of historical evolution, current progress, challenges, and prospects - Muhammad Mubashar; Rabail Zulekha; Muhammad Muzamil Sultan; Pengfei Cheng; Wenguang Zhou; Xuezhi Zhang (Journal of Water Process Engineering, 2026)

Epigenetic regulation under light and temperature fluctuations: chromatin remodeling and transcriptional memory in plants - Bushra Ahmed Alhammad; Muhammad Mubashar Zafar; Shiah M. Alasimi; Mahmoud F. Seleiman (Plant Cell Reports, 2026)

New bovid fossils from the Dhok Pathan, Middle Siwalik subgroup of Pakistan - Kiran Aftab; Bilawal Ghafoor; Muhammad Akbar Khan; Muhammad Adeeb Babar; Mubashar Hussain; Shamaila Irum (PalZ, 2026)

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Morphology and phylogeny reveal four new species and a new record of Volvariella from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Fazli Maula; Wajahat Akram; Abdul Rehman Niazi; Qudsia Firdous; Irmgard Krisai-Greilhuber; Mubashar Raza (New Zealand Journal of Botany, 2025)

Effect of a carbohydrate-rich diet on kidney ultrastructure in albino rats exposed to heat and humidity stress - Robina Shaukat; Muhammad Mubashar Shaukat; Husna Ahmad; Nabila Roohi; Sajjad-ur -Rahman; Rifat Ullah Khan (International Journal of Biometeorology, 2025)

Financial footsteps and carbon footprints: Analyzing the relationship between financial development and carbon inequality in China - Mubashar Humayon; Muhammad Shahbaz; Zokir Mamadiyarov (Journal of Environmental Management, 2025)

Functionalized ZIF-8@ZrP nanohybrid for corrosion- and weathering-resistance epoxy composite coating: Critical role of polyaspartic acid - Yiqian Lv; Jingmao Zhao; Baomin Fan; Muhammad Mubeen; Mahmood Mubashar; Fangze Zi; Yinxin Liu; Wanling Wang; Muhammad Jawad; Xuan Wang; Shuai Liu (Chemical Engineering Journal, 2025)

Designing MgAlCe-Adenine LDH@g-C3N4 nanohybrid integrated polypropylene for bi-functional flame retardancy and corrosion protection - Salman Khalid; Jun Sun; Xinyu Chen; Mohammad Tabish; Mubashar Mahmood; Muhammad Mubeen; Yangming Zou; Zhenhua Wang; Xiaoyu Gu; Jingmao Zhao; Ghulam Yasin; Sheng Zhang (Chemical Engineering Journal, 2025)

Comparative Effects of Antibiotic and Antimicrobial Peptide on Growth Performance, Gut Morphology, Intestinal Lesion Score, Ileal Microbial Counts, and Immune Status in Broilers Challenged with Necrotic Enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Naveed Ul Haque; Muhammad Umar Zafar Khan; Sohail Ahmad (Probiotics and Antimicrobial Proteins, 2025)

Liver response to heat and humidity stress in high fat diet fed rats: a biochemical and histological investigation - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad ur Rahman; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Sifa Dai (International Journal of Biometeorology, 2025)

N-acetylcysteine as a feed additive to counteract ochratoxin A toxicity in poultry - Muntaha Tanveer; Muhammad Imran; Muhammad Kashif Saleemi; Mubashar Shareef; Muhammad Imran; Saqib Umar (Food Additives & Contaminants: Part A, 2025)

Correction to: Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Investigation of the genesis and intensification of simultaneous cyclones in the Arabian sea and Bay of Bengal in November 2020 - Abhishek Kumar; Arun Chakraborty; Mansour Almazroui; Muhammad Mubashar Dogar; Irfan Ur Rashid; Muhammad Adnan Abid; Moetasim Ashfaq (Theoretical and Applied Climatology, 2025)

Carbon quantum dots as versatile nanomaterials for improving soil health and plant stress tolerance: a comprehensive review - Nida Andleeb; Saira Zafar; Zainab Rahim; Muhammad Mubashar Iqbal; Rattan Lal; Muhammad Ansar Farooq (Planta, 2025)
Main conclusion This review summarizes the synthesis, purification/separation, and characterization techniques for carbon quantum dots (CQDs) and highlights their versatile applications as low-toxicity, multifunctional nanomaterials with particular focus on improving soil health, plant stress tolerance, and promoting sustainable agriculture. Abstract Carbon quantum dots (CQDs) have recently emerged as highly versatile nanomaterials with a broad spectrum of applications. This review provides a comprehensive overview of various aspects of CQDs, including their synthesis via both top–down and bottom–up approaches, along with the critical separation and purification techniques required to fully harness their potential. This article highlights the multifaceted roles of both pristine and engineered CQDs in soil and plant systems, with a particular emphasis on soil biochemical processes and different stages of plant life cycle. A special attention has been given to the role of CQDs in enhancing plant tolerance to various biotic and abiotic stresses, such as nutritional imbalance, salinity, drought, heat, and heavy metal stress, with studies showing an improvement in stress tolerance, and considerable increase in seed germination rates when seeds are primed with CQDs. We have also discussed the crucial role of CQDs-mediated gene delivery in plants along with their influence on various soil characteristics. Moreover, the application of CQDs in the detection of agrochemical residues has been discussed with detection sensitivity reported as low as 0.1 µg L −1 for certain pesticides along with their broader utility in environmental remediation, food safety, and therapeutic applications demonstrating their unique properties and multi-functionality for sustainable use. This review also addresses the emerging concerns surrounding the potential toxicity of CQDs, particularly in plants, the food chain, and human health. While most studies report low toxicity at concentration below 100 mg L −1 , understanding these risks is important to ensure the safe deployment of CQDs in real-world scenarios. In short, advanced research knowledge is provided as a basis for CQDs future development research toward efficient non-toxic delivery system for sustainable agriculture and other applications. Highlights Comprehensive exploration of synthesis methodologies for CQDs. The multifaceted role of CQDs in improving soil health and plant stress tolerance is discussed. Explores the nutritional significance of CQDs-coated fertilizers and their potential to revolutionize agricultural practices. Highlights the diverse application of CQDs in environmental remediation and biomedical field, emphasizing their cross disciplinary impact. Graphical abstract

When low-dimensional nanomaterials meet polymers: A promising configuration for flame retardancy and corrosion protection - Salman Khalid; Muhammad Mubeen; Mohammad Tabish; Muhammad Jawad; Muhammad Uzair Malik; H.M. Ahsen Ilyas; Mubashar Mahmood; Mohammed Mujahid Alam; Jun Sun; Ghulam Yasin (Chemical Engineering Journal, 2025)

A comprehensive 120-year assessment of drought dynamics and climate teleconnections in Odisha, India (1901–2020): insights from SPI and trend evaluation - Rajkumar Guria; Sanjeev Dwivedi; Pujyasmita Nayak; Shreerup Goswami; Richarde Marques da Silva; Celso Augusto Guimarães Santos; Prakash Chandra Dash; Manoranjan Mishra; Muhammad Mubashar Dogar; Gowhar Meraj; Mansour Almazroui (Natural Hazards, 2025)

Innovative drought monitoring: development and application of the multi-regional aggregated standardized drought index (MRASDI) - Asad Ellahi; Ibrahim A. Nafisah; Mohammed M. A. Almazah; Nafisa A. Abasheir; Ijaz Hussain; Muhammad Mubashar Dogar (Earth Science Informatics, 2025)

Effects of replacing antibiotics with probiotics and antimicrobial peptides on performance, gut health, carcass traits, meat quality, and welfare in broilers infected with Eimeria and Clostridium perfringens - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Suleman; Muhammad Shabir Shaheen; Muhammad Shahbaz Zafar; Sohail Ahmad (Tropical Animal Health and Production, 2025)

Integrative taxonomy and multigene phylogeny uncover three novel taxa of the genus Clitopilus from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Wajahat Akram; Fazli Maula; Fahim Ullah; Momal Batool; Mohsin Ullah; Irmgard Krisai-Greilhuber; Mubashar Raza (Mycological Progress, 2025)

The role of nitric oxide and nitrogen in mediating copper stress in Brassica juncea L. - Bilal A. Rather; Asim Masood; Fei Qiao; Xuefei Jiang; Muhammad Mubashar Zafar; Hanqing Cong; Nafees A. Khan (Plant Science, 2025)

Comprehensive Assessment of Water Quality of a Transboundary River in Nepal Using Hydro-Chemical, Chemometric, Health Risk and Index-Based Approaches - Ramesh Raj Pant; Memet Varol; Mahesh Prasad Awasthi; Rupesh Bohara; Sudip Paudel; Jharana Nepal; Siddha Raj Pant; Tark Raj Joshi; Kiran Bishwakarma; Mansour Almazroui; Muhammad Mubashar Dogar; Rabin Chakrabortty (Water, Air, & Soil Pollution, 2025)
In this study, advanced hydro-chemical analysis, chemometric techniques, health risk assessment and various indices were used to comprehensively assess the water quality of Mahakali River, which is an essential water resource for Nepal and India. Most parameters measured in the water samples collected from 25 sites in the basin during the pre- and post-monsoon periods were found to be compliance with drinking water standards, except NH 4 + and Fe. The Water Quality Index values classified both the main river and its tributary (Chameliya River) as “unsuitable” for drinking. Nutrient pollution was found to be more severe in the tributary, which is much more affected by anthropogenic activities than the main river. Hydro-chemical analysis showed that the dominant water type in the basin is Ca–HCO 3 , which is mainly controlled by rock weathering. Apart from the magnesium hazard index, other irrigation indices confirmed that the surface water of the study area is suitable for agriculture. Chemometric methods provided deeper insights into the water chemistry of the basin by revealing pollution sources and relationships between parameters. Health risk assessment revealed minimal adverse health effects for children and adults exposed to NO 3 –N, Fe and F − . This pioneering study not only provides a holistic evaluation of water quality in a Himalayan glacier-fed river system but also establishes an innovative framework for sustainable water management in climate-sensitive regions worldwide.

Long-term grass lawn management increases soil organic carbon sequestration and microbial carbon use efficiency - Muhammad Nadeem Ashraf; Irfa Mehmood; Zia Ur Rahman Farooqi; Muhammad Itazaz Hassan; Muhammad Sanaullah; Muhammad Mubashar Zafar; Khalid M. Elhindi (Environmental Monitoring and Assessment, 2025)

Triacontanol Improves Arsenic Stress Tolerance in Triticum aestivum L. Varieties by Modulating Secondary Metabolites, Antioxidant Defense System and Grains’ Nutritional Contents - Hafiz Muhammad Mubashar Ali; Shagufta Perveen (Journal of Soil Science and Plant Nutrition, 2025)

An assessment of the autotrophic/heterotrophic synergism in microalgae under mixotrophic mode and its contribution in high-rate phosphate recovery from wastewater - Rabail Zulekha; Muhammad Mubashar; Muhammad Muzamil Sultan; Zimin Wang; Jing Li; Xuezhi Zhang (Bioresource Technology, 2024)

Heterostructured melamine resin Spheres@GO reinforced epoxy composite achieving robust Corrosion-Resistance of Zn-Al-Mg coated steel for automotive applications - Muhammad Mubeen; Jingmao Zhao; Mohammad Tabish; Jingbao Wang; Mubashar Mahmood; Hassan Murtaza; Muhammad Jawad; Baomin Fan; Ghulam Yasin (Chemical Engineering Journal, 2024)

Nuclear integration of MYB36 and APX-1 genes impart heat tolerance in wheat - Hina Firdous; Arfan Ali; Muhammad Mubashar Zafar; Faiz Ahmad Joyia; Muhammad Hamza; Abdul Razzaq; Muhammad Uzair; Sezai Ercisli; Waqas Shafqat Chattha; Mahmoud F. Seleiman; Naeem Khan; Xuefei Jiang (Functional & Integrative Genomics, 2024)

Retraction Note: Assessing green financing with emission reduction and green economic recovery in emerging economies - Miaonan Lin; Haorong Zeng; Xin Zeng; Muhammad Mohsin; Syed Mubashar Raza (Environmental Science and Pollution Research, 2024)

Corrigendum to “Defect-engineered dual Z-scheme core-shell MoS2/WO3-x/AgBiS2 for antibiotic and dyes degradation in photo and night catalysis: Mechanism and pathways” [Environ. Pollut. 356 (2024) 124375] - Muhammad Abbas; Mubashar Ilyas; Kashif Hussain; Tariq Ali; Muhammad Afzal; Nazia Batool; Navid Hussain Shah; Muhammad Qasim; Yaling Wang; Yanyan Cui (Environmental Pollution, 2024)

Defect-engineered dual Z-scheme core-shell MoS2/WO3-x/AgBiS2 for antibiotic and dyes degradation in photo and night catalysis: Mechanism and pathways - Muhammad Abbas; Mubashar Ilyas; Kashif Hussain; Tariq Ali; Muhammad Afzal; Nazia Batool; Navid Hussain Shah; Muhammad Qasim; Yaling Wang; Yanyan Cui (Environmental Pollution, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Bio-formulated chitosan nanoparticles enhance disease resistance against rice blast by physiomorphic, transcriptional, and microbiome modulation of rice (Oryza sativa L.) - Rahila Hafeez; Junning Guo; Temoor Ahmed; Hubiao Jiang; Mubashar Raza; Muhammad Shahid; Ezzeldin Ibrahim; Yanli Wang; Jiaoyu Wang; Chengqi Yan; Qianli An; Jason C. White; et al. (Carbohydrate Polymers, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

The synergetic impact of digital campaigns and economic incentives on environmental performance: the mediating role of household indoor and outdoor activities - Shahzad Ali; Muhammad Boota; Warda Sajid Khan; Mehrooz Khan; Mubashar Ali (Environmental Science and Pollution Research, 2024)

Middle Miocene “Giraffa” from the Chinji Formation of Siwaliks, Pakistan - Muhammad Asim; Kiran Aftab; Muhammad Akbar Khan; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Mubashar Hussain; Sania Saeed (Palaeoworld, 2024)

Whether water exchange is an effective solution for emergency mitigation of algae bloom - Haiyang Zhang; Yongpeng Wang; Jing Li; Xin Chen; Muhammad Mubashar; Shouchun Li; Xuezhi Zhang (Journal of Water Process Engineering, 2024)

Influence of algal organic matter in the in-situ flotation removal of Microcystis using positively charged bubbles - Shaozhe Cheng; Haiyang Zhang; Hailing Wang; Muhammad Mubashar; Lili Li; Xuezhi Zhang (Bioresource Technology, 2024)

Carbon-negative and high-rate nutrient recovery from municipal wastewater using mixotrophic Scenedesmus acuminatus - Muhammad Mubashar; Rabail Zulekha; Shaozhe Cheng; Cong Xu; Jing Li; Xuezhi Zhang (Journal of Environmental Management, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Progress in genome-wide identification of RBPs and their role in mitigating stresses, and growth in plants - Muhammad Haroon; Hala Tariq; Rabail Afzal; Muhammad Anas; Shanza Nasar; Neha Kainat; Sajid Fiaz; Uswa Irfan; Fahad Idrees; Muhammad Mubashar Zafar (South African Journal of Botany, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Effects of Saccharomyces cerevisiae live cells and culture on growth and productive performance in lactating Nili-Ravi buffaloes - Mohsin Ali; Saeed Ahmed; Mubashar Ali; Nisar Ahmad; Mohammad Noman Tariq; Muhammad Usman; Ahmad Azeem Sardar (Tropical Animal Health and Production, 2023)

Exogenous application of melatonin alleviates the drought stress by regulating the antioxidant systems and sugar contents in sorghum seedlings - Ahmad Sher; Muhammad Umair Hassan; Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Zara Hayyat; Yamin Bibi; Mubashar Hussain; Abdul Qayyum (Biochemical Systematics and Ecology, 2023)

RETRACTED ARTICLE: Assessing green financing with emission reduction and green economic recovery in emerging economies - Miaonan Lin; Haorong Zeng; Xin Zeng; Muhammad Mohsin; Syed Mubashar Raza (Environmental Science and Pollution Research, 2023)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Assessment of pathogenicity of Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringiensis var. kurstaki against Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) via diet-bioassay technique under controlled conditions - Mubashar Iqbal; Muhammad Dildar Gogi; Bilal Atta; Muhammad Junaid Nisar; Muhammad Jalal Arif; Nazir Javed (International Journal of Tropical Insect Science, 2021)

Variation of main rainy‐season precipitation in eastern China and relevance to regional warming - Li Liu; Xiaojuan Wang; Guolin Feng; Muhammad Mubashar Dogar; Feng Zhang; Gong Zhiqiang; Botao Zhou (International Journal of Climatology, 2021)
China has experienced dramatic warming in summer mean temperature since the early 1990s, leading to precipitation variation across the region. We have studied the variation of rainy‐season (April–September) precipitation in eastern China during 1961–2016. Overall, we found that rainy‐season precipitation increased in the south and decreased in the north during 1992–2016 (PII) compared to 1961–1991 (PI). By defining rainfall‐belt indices of intensity and central location, we found that the southern rainfall‐belt during the main rainy‐season tends to produce much more‐intense precipitation during PI relative to PII, in contrast to the northern rainfall‐belt, which tends to have less‐intense precipitation during PII. Despite some fluctuations, the central positions of neither the northern nor the southern rainfall‐belts exhibit a statistically significant difference between the two periods. Unlike during PI, during PII, there is an obvious anticyclone over the Lake Baikal region. This anticyclone has caused anomalous north winds flowing from north‐central to southwestern China, leading to weakening of the northward moisture transport. Also, regions such as northeastern, north‐central, and southwestern China have been controlled by negative geopotential height anomalies and weak vertical air‐motion anomalies, resulting in drying from north to southwestern China. At the same time, the enhanced water‐vapour convergence in the southeastern coastal region of China favours increased precipitation there. These processes working in concert created the drying‐north–wetting‐south pattern in the main rainy‐season during 1961–2016. The change in rainfall‐belt intensity in eastern China has also shown a close relationship with the change in vapour transport from low latitudes. The weakened land‐sea thermal difference in the East Asia–Northwest Pacific region, which has weakened water‐vapour and atmospheric circulation, has also played a role in the change of rainfall‐belt intensity.

Variability and Predictability of Summer Monsoon Rainfall over Pakistan - Muhammad Adnan; Firdos Khan; Nadia Rehman; Shaukat Ali; Sher Shah Hassan; Muhammad Mubashar Dogar; Shahbaz Mehmood; Shabehul Hasson (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Impacts and evaluation of Hormoligosis of some insect growth regulators on Phenacoccus solenopsis (Hemiptera: Pseudococcidae) - Muhammad Idrees; Muhammad Dildar Gogi; Waqar Majeed; Arbab Yaseen; Mubashar Iqbal (International Journal of Tropical Insect Science, 2020)

The mechanism of EAP-EU combined impact on summer rainfall over North Asia - Po Hu; Jianbo Cheng; Guolin Feng; Muhammad Mubashar Ahmad Dogar; Zhiqiang Gong (Theoretical and Applied Climatology, 2020)

Effect of foliar applied triacontanol on wheat (Triticum aestivum L.) under arsenic stress: a study of changes in growth, yield and photosynthetic characteristics - Hafiz Muhammad Mubashar Ali; Shagufta Perveen (Physiology and Molecular Biology of Plants, 2020)

Joint Effect of East Asia-Pacific and Eurasian Teleconnections on the Summer Precipitation in North Asia - Po Hu; Guolin Feng; Muhammad Mubashar Dogar; Jianbo Cheng; Zhiqiang Gong (Journal of Meteorological Research, 2020)

Fighting against fall armyworm by using multiple genes pyramiding and silencing (MGPS) technology - Maozhi Ren; Muhammad Mubashar Zafar; Huijuan Mo; Zhaoen Yang; Fuguang Li (Science China Life Sciences, 2019)

The possible physical mechanism for the EAP–SR co-action - Zhiqiang Gong; Guolin Feng; Muhammad Mubashar Dogar; Gang Huang (Climate Dynamics, 2018)

Introgression and inheritance of charcoal rot (Macrophomina phaseolina) resistance from silver sunflower (Helianthus argophyllus Torr. & A. Gray) into cultivated sunflower (Helianthus annuus L.) - Muhammad Shehbaz; Saeed Rauf; Abdullah M. Al-Sadi; Shahid Nazir; Saira Bano; M. Shahzad; Muhammad Mubashar Hussain (Australasian Plant Pathology, 2018)

Enhancement of Dissolution and Skin Permeability of Pentazocine by Proniosomes and Niosomal Gel - Asadullah Madni; Muhammad Abdur Rahim; Muhammad Ahmad Mahmood; Abdul Jabar; Mubashar Rehman; Hassan Shah; Arshad Khan; Nayab Tahir; Aamna Shah (AAPS PharmSciTech, 2018)

Assessment and correction of BCC_CSM's performance in capturing leading modes of summer precipitation over North Asia - Zhiqiang Gong; Muhammad Mubashar Dogar; Shaobo Qiao; Po Hu; Guolin Feng (International Journal of Climatology, 2018)
This article examines the ability of Beijing Climate Center Climate System Model (BCC_CSM) in demonstrating the prediction accuracy and the leading modes of the summer precipitation over North Asia (NA). A dynamic‐statistic combined approach for improving the prediction accuracy and the prediction of the leading modes of the summer precipitation over NA is proposed. Our results show that the BCC_CSM can capture part of the spatial anomaly features of the first two leading modes of NA summer precipitation. Moreover, BCC_CSM regains relationships such that the first and second mode of the empirical orthogonal function (EOF1 and EOF2) of NA summer precipitation, respectively, corresponds to the development of the El Niño and La Niña conditions in the tropical East Pacific. Nevertheless, BCC_CSM exhibits limited prediction skill over most part of NA and presents a deficiency in reproducing the EOF1's and EOF2's spatial pattern over central NA and EOF2's interannual variability. This can be attributed as the possible reasons why the model is unable to capture the correct relationships among the basic climate elements over the central NA, lacks in its ability to reproduce a consistent zonal atmospheric pattern over NA, and has bias in predicting the relevant Sea Surface Temperature (SST) modes over the tropical Pacific and Indian Ocean regions. Based on the proposed dynamic‐statistic combined correction approach, compared with the leading modes of BCC_CSM's original prediction, anomaly correlation coefficients of corrected EOF1/EOF2 with the tropical Indian Ocean SST are improved from 0.18/0.36 to 0.51/0.62. Hence, the proposed correction approach suggests that the BCC_CSM's prediction skill for the summer precipitation prediction over NA and its ability to capture the dominant modes could be certainly improved by choosing proper historical analogue information.

Development of Eudragit RS 100 Microparticles Loaded with Ropinirole: Optimization and In Vitro Evaluation Studies - Prince Muhammad Kashif; Asadullah Madni; Muhammad Ashfaq; Mubashar Rehman; Muhammad Ahmad Mahmood; Muhammad Imran Khan; Nayab Tahir (AAPS PharmSciTech, 2017)

Study of the global and regional climatic impacts of ENSO magnitude using SPEEDY AGCM - Muhammad Mubashar Dogar; Fred Kucharski; Syed Azharuddin (Journal of Earth System Science, 2017)